Problems of alcoholization as a distributed form of addictive behavior of minors (Journal of actual problems of jurisprudence, 2019)
Solving the problem of combating alcohol abuse in minors seems to be the most effective only by studying the patterns of genesis and the further development of the mechanism of addiction and addictive forms of behavior, one of which is the alcoholization of minors. The analysis of addiction and addictive forms of behavior makes it possible to understand their real place in the structure of public relations, to predict the consequences of their distribution and to take measures to eliminate these negative phenomena. Antisocial behavior of a minor in the form of alcoholism is interconnected by the influence of various factors, primarily the external social environment (especially the microenvironment), as well as the individual characteristics of the minor’s personality, which cause his individual response to various life problems, independent solving which for a minor is problematic. Key words: minor, addict, addiction, addictive behavior, alcoholism, sociological survey, prophylaxis, prevention, control measures, anti-alcohol policy.